ANALISIS TINGKAT KESEHATAN BANK PADA PT. BANK PERMATA TBK PERIODE 2010-2011 - Laluyan, Marlyn Pricillia (EKONOMIA, 2012)
Bank soundness can be defined as the ability of a bank to conduct normal banking operations and is able to meet all its obligations well in ways that conform to the applicable banking regulations. To determine healthy or unhealthy can be analyzed through several aspects, namely CAMEL (Capital, Assets, Management, Earnings, and Liquidity). This study aims to determine the level of health of PT. Bank Permata Tbk in 2010 and 2011 by using the CAMEL analysis. The data used is the consolidated financial statements for 2010-2011. As a measure to determine the soundness of a bank after an assessment of each component of CAMEL which is a variable of the study, namely to determine the outcome of the assessment is classified into bank health ratings. The results showed that the level of health of PT. Bank Permata Tbk period 2010-2011 are included in the category of fairly healthy. Assessment of the level of health in 2010 are included in the category of fairly healthy for a total credit of 78.31 and in 2011 was included in the category is quite healthy for a total credit of 76.89.